Analysis of Channel Evolution and Its Influence of Xunwu River in Source Area of Dongjiang River Based on GIS Technology - CHEN Chuan; ZENG Jinfeng (Renmin Zhujiang)
Based on the measured data of large fixed sections at Shuibei Hydrological Station from 2010 to 2020 and the underwater topographic survey data near Shuibei Hydrological Station,this paper constructs a topographic database of underwater sections and a three-dimensional underwater topographic model near Shuibei Hydrological Station for riverbed change analysis by using GIS technology,analyzes the channel scouring and silting in single Shuibei Station section of the main stream of Xunwu River in terms of temporal and spatial change,and discusses the influencing factors and the influence of the changes.The results show that:GIS technology is an effective method to study the changes of river topography.The average annual river-bed elevation of Shuibei Station section of the main stream of Xunwu River decreased by 0.75 m from 2010 to 2015,and by 0.52 m from 2015 to 2020.With the scouring of the main channel terrain during 2010—2020,the average undercut depth is 1.27 m.The main factors for the topographic change of the river channel in this section are the sand restraining of power plants,the sand mining of river channels and the comprehensive treatment of abandoned mines.The annual undercut of river channels will increase the storage capacity of river channels and increase the reverberation time of pollutants in the downstream channels,thus worsening the water quality.In a worse case,the severe evolution of riverbed may cause the dangerous situation of the bridge across the river and even the hollowing out or collapse of embankment.